Learning, as a wonder weapon of endogenous growth? - Péter Mihályi (Hungarian Academy of Sciences, Institute of Economics, 2017)
This extended book review of Creating a Learning Society by Joseph Stiglitz and Bruce Greenwald (2014) looks at the 700-page long scholarly work from a transition economy perspective. Using as a starting point Arrow's renowned concept of "learning by doing", the authors throw away the doctrines of free trade, liberalization of capital, as well as the liberalization of labour and currency markets (for short: the Washington consensus) by claiming that these policies imped economy-wide learning. In the opinion of the present author, Stiglitz and his co-author are using the term "learning" in such a broad sense that it becomes almost meaningless as an explanatory factor in their endogenous growth concept thought out primarily for less developed (infant) economies.
Keywords: E61; E71; F12; I26; I28; 330; Infant industry; infant economy; learning; labour productivity; inertia; rivalry; Washington consensus